Dynamics.n adolescents - A. A. Pichikov; Y. V. Popov; Y. A. Jakovleva (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева)
The article discusses the self-injurious behavior among adolescents. Analyzed the dynamics of self-injurious behavior during the two-year follow-up among adolescents with different clinical diagnosis and determined the characteristics of suicidal fantasy relationship with the formation of suicidal tendencies.